Anatomical assessment of foramen tympanicum using cone beam computed tomography images - Parastoo Afghari; Roshanak Ghaffari; Saeed Sohilipour (Wolters Kluwer Medknow Publications, 2016)
Introduction: Foramen tympanicum is a normal variation of tympanic plate of the temporal bone which exists in the tympanic plate at birth time and will rarely remain open through adulthood. The aim of this research study is to assess the prevalence of this foramen in people over 6 years of age. Materials and Methods: In this descriptive-analytic planned cross-sectional study, cone beam computed tomography (CBCT) images of 159 patients (318 ears) over 6 in the Isfahan Province during 2015-2016 were evaluated. The foramen was detected in the axial plane and then was confirmed on the other planes. On each image, the location, size, and configuration of the foramen were studied. Patients were asked about the symptoms in case the foramen was detected. Finally, the data were analyzed using the Chi-square test, independent t-test, McNemar, Fisher, and Pearson correlation coefficient (P > 0.05). Results: A total of 159 images of the patients aged 6-78 years including 99 males and 60 females were studied, of which 11 patients (6.9%) had at least the foramen on one side. The foramen prevalence was symmetrical on both sides (5%), but the tympanic plate's thinning was significantly higher on the right side (11.3%) than on the left side (5.7%) (P = 0.04). The general shape of the foramen seemed to be oval when axial and sagittal diameters were compared. Statistical analysis indicated a negative correlation between patients' age and the foramen diameter (P = 0.03, r = −0.324). Conclusion: Using high-resolution CBCT images, the prevalence of the foramen tympanicum in people over 6 in Isfahan was found to be 6.9% and symmetrical in the two sides and in both genders.